Deleterious AHNAK2 Mutation as a Novel Biomarker for Immune Checkpoint Inhibitors in Non-Small Cell Lung Cancer - Cui, Yanan; Liu, Xinyin; Wu, Yuemin; Liang, Xiao; Dai, Jiali; Zhang, Zhihong; Guo, Renhua (Frontiers in Oncology, 2022)
Immune checkpoint inhibitors (ICIs) have exhibited promising efficacy in non-small cell lung cancer (NSCLC), but the response occurs in only a minority of patients. In clinic, biomarkers such as TMB (Tumor mutation burden) and PD-L1 (Programmed cell death 1 ligand 1) still have their limitations in predicting the prognosis of ICIs treatment. Hence, reliable predictive markers for ICIs are urgently needed. A public immunotherapy dataset with clinical information and mutational data of 75 NSCLC patients was obtained from cBioPortal as the discovery cohort and another immunotherapy dataset of 249 patients across multiple cancer types was collected as the validation. Integrated bioinformatics analysis was performed to explore the potential mechanism and immunohistochemistry studies were used to verify it. AHNAK nucleoprotein 2 (AHNAK2) was reported to have pro-tumor growth effects across multiple cancers, while its role in tumor immunity was unclear. We found that approximately 11% of the NSCLC patients harbored AHNAK2 mutations, which were associated with promising outcomes to ICIs treatments (ORR, P=0.013). We further found that AHNAK2 deleterious mutation (del-AHNAK2mut) possessed better predictive function in NSCLC than non-deleterious AHNAK2 mutation (PFS, OS, log-rank P<0.05), potentially associated with stronger tumor immunogenicity and activated immune microenvironment. This work identified del-AHNAK2mut as a novel biomarker to predict favorable ICI response in NSCLC.